Siderophore screening in marine sponge extracts using LC-HRMS and an R-based metabolomics workflow - Alejandro García Ríos; Massuo Jorge Kato; Lydia Fumiko Yamaguchi; Breno Pannia Espósito; Ailan Farid Arenas-Soto (PLoS ONE, 2026)
Siderophores are pivotal ‌‌iron-acquisition biomolecules integral to microbial survival, pathogenicity, and ecology. Elucidating these compounds offers critical insights into the microbial dynamics of marine holobionts and potential therapeutic applications. In this study, we present a culture-independent, data-centric strategy to annotate siderophores from the body mass of three marine sponge species: Dragmacidon reticulatum , Aplysina fulva , and Amphimedon viridis . Utilizing Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS) coupled with a custom R-based analytical workflow (XCMS and MetaboAnnotation), we putatively annotated 59 siderophores. We employed a validation pipeline, utilizing iron-adduct calculations [M-2H + Fe] + , [M-H + Fe] 2+ , [2M-2H + Fe] + , mass accuracy thresholds (<3 ppm), retention time deviation (Coefficient of variation < 2%), and chromatograph peak analysis. According to the Metabolomics Standards Initiative (MSI), these annotations correspond to Level 2 (putatively annotated compounds) because they are based on accurate mass matching without chemical standard confirmation. Notably, iron supplementation during extraction did not significantly alter siderophore detection, suggesting constitutive production or environmental saturation. This workflow bypasses the limitations of traditional cultivation, revealing a diverse landscape of iron-chelating metabolites, including Ferricrocin, Aeruginic acid, and Madurastatin directly within the sponge’s body.